Antimicrobial Activity and GLC Analysis of the Essential Oil of the Leaves of Eupatorium triplinerve - Yadav, R.N.; Barsainya, Deepak (Asian Journal of Chemistry, 2010)
In the present paper, the authors describe the antimicrobial activity andGLC analysis of the essential oil of the leaves of Eupatorium triplinerve.